Case report of serial pleural effusion managed with good fetal outcome - I. Patel, Shreya; Patel, Priyadatt; Choudhary, Mayank; Jhala, Meena; Thakkar, Harmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Fetal pleural effusion is a rare congenital anomaly that occurs when some amount of fluid surrounds the fetal lung without concomitant hydrops. It may remain the same or progress more. We present here a case of a 32-year-old lady with primary infertility who conceived naturally. She presented to us for her routine term pregnancy evaluation. At 17 weeks her targeted imaging for fetal anomalies (TIFFA) scan revealed left side severe fetal hydrothorax. Again at 29 weeks left pleural effusion was noted. A C-section was performed at 38th week of pregnancy and a male child weighing 2.995 grams was born, with no need for ventilator support.